EVALUATION OF THE EFFECTIVENESS OF CLOCKWISE ROTATION OF THE MAXILLOMANDIBULAR COMPLEX IN THE SURGICAL CORRECTION OF CLASS III MALOCCLUSION AT VAN HANH GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Conventional orthognathic surgery sometimes fails to achieve optimal aesthetic results in Class III malocclusion patients with a low occlusal plane angle. Clockwise rotation of the Maxillo-Mandibular Complex (MMC) has been implemented to address aesthetic limitations in these cases. However, existing evidence primarily focuses on isolated patient groups and remains limited in Vietnam.Objective: To evaluate the changes in hard and soft tissues following clockwise MMC rotation surgery in the treatment of Class III skeletal malocclusion.Materials and Methods: A retrospective longitudinal descriptive study was conducted on 30 patients (9 males, 21 females; mean age 25) diagnosed with Class III skeletal malocclusion who underwent preoperative orthodontics and clockwise MMC rotation surgery. Cephalometric measurements were performed at three stages: preoperative (T1), one week postoperative (T2), and six months postoperative (T3). Hard tissue changes were assessed using T2–T1, while soft tissue changes were evaluated via T3–T1.Results: Postoperatively, skeletal parameters showed statistically significant changes (p < 0.05) the ANB angle increased, achieving a Skeletal Class I relationship; the mandibular plane angle (MP-SN) increased, reflecting a downward and backward rotation of the mandible. Regarding soft tissues, the nasolabial angle and facial contour angle increased significantly, resulting in a more harmonious facial profile.Conclusion: Clockwise rotation of the maxillo-mandibular complex is an effective method for treating Class III malocclusion. It significantly improves facial profile aesthetics by increasing maxillary incisor display and midface prominence.
Keywords: Class III malocclusion, Orthognathic surgery, Maxillomandibular complex rotation, Clockwise rotation.